DEVELOPMENT STRATEGY FOR ALLANG ASAUDE BEACH TOURISM, HUAMUAL BELAKANG DISTRICT, WEST SERAM REGENCY - Haryanto, Djeny; Yuliana, Ernik; Sulistyowati, Lilik (Jurnal Segara, 2025)
Coastal areas play a crucial role in supporting tourism, local economies, and the conservation of natural resources; therefore, sustainable management based on suitability and environmental carrying capacity data is essential. This study aims to analyze the level of suitability and carrying capacity of the coastal tourism area at Allang Asaude Beach, Huamual Belakang District, West Seram Regency, Maluku Province. Data was collected through direct observation and open-ended interviews. The assessment of coastal tourism suitability employed ten parameters, including beach type, beach width, substrate material, water depth, clarity, current velocity, beach slope, land cover, presence of hazardous biota, and availability of freshwater. The results showed that the coastal tourism suitability index at three observation stations fell into the highly suitable category, with an Index of Tourism Suitability (ITS) value of 2.99. The supporting biophysical conditions such as clear waters, calm currents, and white sandy beaches were the main determinants of this classification. Meanwhile, the Carrying Capacity (CC) calculation indicated that the Allang Asaude coastal tourism area could accommodate up to 1,363 visitors per day, remaining within the safe ecological threshold. These findings suggest that Allang Asaude Beach has excellent potential to be developed as a sustainable marine tourism destination, provided that environmental management, conservation principles, and local community participation are effectively implemented.